A Qualitative Approach for Investigating Thermal Discomfort in the Outdoor Environment of a World Heritage Site: A Case Study of Hampi, India - Paul, Tanaya; Daketi , Srinivas; Rao M, Kailasa; Chundeli , Faiz Ahmed (Geographica Pannonica, 2025)
The outdoor thermal environment affects visitors’ thermal comfort and overall experience. This study investigates the application of photographic analysis as a qualitative tool for evaluating thermal discomfort in outdoor environments at a World Heritage Site. Thermal discomfort is a key concern in public settings as global temperatures continue to rise. At the same time, traditional approaches rely on microclimate measurements and user feedback. However, this study takes a more subjective, visual approach to capturing and interpreting how visitors experience thermal comfort or discomfort in large-scale archaeological sites. This research uses photographic data to identify and analyze the primary visual signs of thermal discomfort. Results reveal that visitors in the heritage site experience strong heat stress during the winter season. Despite the study area experiencing strong heat stress and visitors feeling hot and warm, the majority of the visitors are satisfied with the thermal conditions of the heritage site. Photographic analysis reports that the most common signs of thermal discomfort are mostly related to intense solar radiation and the absence of shade. The research findings can be used to develop strategies for reducing thermal discomfort while maintaining the cultural and historical integrity of heritage places. The research underscores the importance of visual data in comprehending the interplay between thermal comfort, environmental design, and visitor experiences in culturally significant sites.